Expansão da rede de unidades de conservação da Mata Atlântica e sua eficacia para a proteção das fitofisionomias e espécies de primatas: análises em sistemas de informação geografica - Andre de Almeida Cunha (2010)
In the last century, massive investments towards biodiversity conservation were applied to the Atlantic forest, particularly for protected areas (PA) creation and management. However, the evaluation of the achivemnets of all these efforts is still scarce. To evaluate the expansion and efficacy of the Atlantic forest protected area network, the first step was to define the most appropriate geopolitical boundaries. This is especially difficult in the Atlantic forest, which congregates a myriad of vegetation types and species, with different phylogeographic histories, under severe destruction and fragmentation along the last five centuries. Additionally, two different boundaries for the Brazilian Atlantic forest were established by federal government, the Domain and the Biome, differing in 235.000 km2. The Atlantic forest Domain includes transition zones outside the Biome boundaries, where species composition are more similar to others biomes than the Atlantic Forest. Thus, the Atlantic Forest Biome is biogeographically more accurate than the Domain. However, according to the current legislation, the remnants outside Atlantic Forest are less protected, and those ones in the transition zones are more scarce, degraded and unprotected than the remnants inside the Biome limits. Considering governments and private sector as the main responsibles for the creation of PAs, it is interesting to analyze the historical investment of these actors towards the establishment of current PA network in the Biome. Socioeconomic and political environment is also highly heterogeneous along the Brazilian Atlantic Forest Biome, as well as the commitment of private sector, states and federal governments towards the creataion of new PAs. Federal government invested in all regions mainly in PAs for strictly protection (SPAs), since late 1930s, but there were only a few state governments creating SPAs, it occurs mainly in the southeastern region, and after the 1960s. Most state governments established, since the 1980s, sustainable use protected areas (SUPAs), despite increasing criticism about the failure of this PA category to biodiversity conservation. Private sector created its PAs (RPPNs) only since the 1990s, however, there was a slow increase in the area of RPPNs network in the last decade, and total area covered by RPPNs are still a small fraction of governments PAs network. Considering that most remnants of the current Atlantic forest are under private properties, new incentives towards the involvement of private sector are needed, such as the payment for ecosystems services (PES) and the implementation of other types of areas under protection in rural properties, such as Legal Reserves and Areas of Permanent Protection. On the other hand, governments must guarantee a representative cover of protected areas. Environmental heterogeneity also needs to be taking into account when setting conservation strategies for the Atlantic forest. In this sense, it is an interesting approach to analyze the conservation status and the protection of the remnants of different vegetation types in the biome. Using the Brazilian Biomes Land Cover Assessment maps and the polygons of current PAs, under different protection categories, it is possible to evaluate the risk of extinction of each vegetation type and the efficacy of SPAs and SUPAs to protect these remnants. With exception to the evergreen forest, all other four forest types are threatened with extinction. Considering only the remnants inside SPAs, all these four forests could be probably extinct in the near future. Currently, land cover indicates SPAs more efficacy to protect the remnants of Atlantic Forest than SUPAs. Actually, 40% of SUPAs encompasses human land cover types. However, SUPAs are newer than SPAs, so this assessment should be considered as a baseline to monitor future changes in the land cover, from restoration or degradation, inside Pas, allowing a better evaluation of PAs efficacy between categories. Extinction risk and protection of the Atlantic forest vegetation types is a useful approach, however must be complemented by assessing other components of biodiversity. Species are good candidates, particularly those species with exceptional importance to ecosystems maintenance and social mobilization towards conservation, such as the primates of the Atlantic forest. Twenty three species occur in the biome, sixteen are endemic and fifteen threatened, mainly due to habitat loss, fragmentation, and hunting. The persistence of these primates in the Atlantic forest landscape depends, mainly, on the efficacy of PAs to protect viable populations. Habitat extension inside PAs and within the distribution range of each species, together with density estimates, were used to calculate potential population sizes of these species in PAs. Eight out of twenty species have less than 1% of their distribution ranges in the available habitat inside PA. Potential population sizes in current PAs network is not enough to guarantee long term viability for most primates in the Atlantic forest. This is even worse considering that population sizes are overestimated for most species. Species under most severe risk of extinction occur in most endangered vegetation types, and in states with a scarce PAs coverage, particularly state SPAs. Thus, protect and restore habitats, for the endangered primates of the Atlantic Forest, is a promising way to conserve the biodiversity and heterogeneity of this biome, especially when considering the importance of these primates as flagship and landscape species. This thesis evidenced that besides all efforts applied, and the expressive expansion of PA network, this was not enough to assure the conservation of Atlantic forest biodiversity. State governments and private sector, with few exceptions, did few contributions to the actual PAs network. Given the current trends of degradation, only a small fraction of vegetation types and primates species are probable to persist in the biome, as probably this is also true for other components of the Atlantic forest biodiversity. The present approach, tools, and results are useful to analyze the expansion and efficacy of PA network, it should assist decision making process and the destination of resources and incentives to biodiversity and ecosystem conservation. Hopefully it could be disseminated, improved, and adjusted to evaluate PA networks in other regions.